Respostas

A melhor resposta!
2013-09-18T16:18:41-03:00
A) (-4*(-3))-(1*8) = 12-8->detA= 4
B)(8*(-7)) - (raiz de 3* raiz de 3) = -56+3->detA= -53
C) (-4*4*8)+(6*6*-1)+(-9*-3*3)-(-9*-3*3)-(-9*4*-1)-(-4*6*3)= -128-36+81-36+72+144->    detA=  97
1 5 1
2013-09-18T16:27:29-03:00
A)  Dp = -4.(-3)
      Dp = 12
      Ds = 8.1
      Ds = 8
 det  = Dp-Ds
det = 12 - 8
det = 4

B) Dp = 8.(-7)
     Dp = -56
     Ds = √3.√3
     Ds =  
√3²
     Ds = 3
det = -56-3
det = -59


C)Usando a regra de Sarrus temos:
Dp = -128+36+81
Dp = -11
Ds = 36-72-144
Ds = -180
det = -11-(-180)
det = -11+180
det = 169

1 5 1